A Needs Analysis for Developing a Short Story Learning Module Based on Gender Equality and Local Identity in Nabire - Happy Dwi Prihartanti; Nazla Maharani Umaya; Sri Suciati (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to analyze the suitability of learning components with gender-responsive principles and to identify the need for developing short story teaching materials based on gender equality and local identity in Nabire Regency. A qualitative descriptive approach was employed, involving Indonesian language teachers and senior high school students in Phase F as research subjects. Data were collected through classroom observations, teacher needs questionnaires, and textbook document analysis, then analyzed using an interactive model comprising data reduction, presentation, and conclusion drawing. The findings reveal that the learning process has not fully reflected gender equality. Inequalities were observed in student participation and role distribution, where male students tended to dominate public activities while female students were confined to domestic roles. Teachers demonstrated a high level of understanding of gender-responsive learning (77.0%); however, implementation remained at a moderate level (58.8%). The need for gender-responsive teaching materials based on local identity was categorized as very high (84.5%). Textbook analysis further showed that existing short story materials inadequately represented gender equality, as evidenced by the dominance of male characters and the limited roles assigned to female characters. This study is a needs analysis; it does not yet encompass the module development stage itself. Nevertheless, its findings provide a critical empirical foundation for designing gender-responsive literary teaching materials tailored to culturally specific regional contexts. The study contributes to Indonesian language pedagogy by documenting a significant and systematic gap between gender awareness, practice, and material availability in a region that has been largely underrepresented in educational research. These findings can directly inform curriculum developers, teacher educators, and school leaders in Nabire and comparable contexts in Eastern Indonesia.